Fatty Acids and Heavy Metal Content of Five Commercial Fishes in Dhaka City (Bioresearch Communications, 2026)
Fish are a staple food for humans, being a rich source of essential fatty acids and may also be a potential sink for heavy metals in urban food chains like those in Dhaka city. Methods: This study was conducted to assess the fatty acid and heavy metal (Pb, Cd, Zn, Cr) concentration of some of the selected commercially available fish species of Dhaka city. Methodology: Five commonly consumed fish species, Ompok bimaculatus (Pabda), Sperata aor (Poa), Otolithoides pama (Ayer), Scomberomorus guttatus (Shurma) and Chitala chitala (Chitol) were selected for this study. The fatty acid profile was determined by the gas chromatography method and the heavy metal content by the atomic absorption spectrophotometry method. Results: The total fat content of the five widely eaten fish species varied considerably, with Pabda being the highest and Poa and Shurma the lowest, and Ayer and Chitol in between. The predominant saturated fatty acid was palmitic acid and the major monounsaturated fatty acid was oleic acid, which was highest in Pabda. Total saturated fat comprised about 37-44% of fatty acids, but total monounsaturated fat was highest in Pabda and lowest in Shurma. Polyunsaturated fat was highest in Shurma and lowest in Pabda, and omega-3 fatty acids (particularly EPA and DHA) were high in Shurma, with Poa and Chitol in between, and lowest in Pabda. Essential fatty acids linoleic acid and linolenic acid were species-dependent, with Pabda having the most linoleic acid, and Chitol and Ayer having relatively more linolenic acid. Evaluation of heavy metals revealed non-detectable cadmium and lead, but variable, species-specific nickel, and particularly high chromium. These common fish species showed species-dependent trade-offs between fat content and heart-protective omega-3s, non-detectable cadmium and lead, but variable nickel and particularly high levels of chromium in some species, highlighting the need for species-specific dietary guidelines and monitoring to ensure heart-healthy benefits but also to avoid risks of heavy metal exposure.Bioresearch Commu. 12(2): 2123-2129, 2026 (January)